Persistent Fetal Vasculature with Pediatric Cataract, Microcornea, Sensory Exotropia and Mental Retardation: A Case Report: Poster Presentation - Case Report - Resident - MADE KUSUMA WARDANI; Dr. dr. Ni Made Ayu Surasmiati, M.Biomed, Sp.M(K); Dr. dr. I Wayan Eka Sutyawan, Sp.M(K); Kevin Anggakusuma Hendrawan; A. A. Dewi Adnya Swari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Persistent Fetal Vasculature (PFV) is a congenital, nonhereditary ocular malformation that frequently involves the lens. PFV is most frequently unilateral. The classical presentation is leukocoria, microphthalmia, and cataract. Case Illustration : A 16-year-old boy patient with mental retardation, came with chief complaint blurred vision and white appearance on the RE, noticed for 1 month ago. Visual acuity of the RE was LPBP and the LE was 6/120. There was microcornea on both eyes with diameter 8 mm. Lens opacity and exotropia with XT 30 0 on the RE. IOP on both eyes was normal. Funduscopic on the RE was negative and LE there was tigroid retina. Ultrasonography of the RE was echogenic with minimal after movement and low to moderate spikes. Planning for this patient were RE lens extraction with IOL. After that evaluate for the posterior segment. Discussion : Progressive cataract formation often occurs, sometimes leading to a complete cataract. Strabismus associated with a unilateral cataract. The most important was differentiating PFV from retinoblastoma. In patients with poor view of the fundus, ultrasonography should be performed. Retinal or optic nerve abnormalities cannot be definitively ruled out, however, until the posterior pole can be visualized directly. The opacity in the affected eye should be cleared to allow visual development and to save the eye from complications of untreated PFV. Conclusion : It is important to obtain a detailed history of the child’s growth, development, systemic disorders, family history, and need further comprehensive examination and multidiscipline consultation to establish the diagnose.